Application of CT Scan in Diagnosis of Iliac-Femoral Vein Thrombosis after Hip Replacement. (20th June 2022) - Li, Dong; Wang, Lishan; Li, Zhanxin; Li, Libin; Wang, Qingwei; Zhang, Li; Guo, Zhigang
Abstract : Based on the knowledge of the previous film, the CT scan was used to diagnose the disease of women and men after the diagnosis of atherosclerosis by scanning the CT microscope. This article first examines the existing medical procedures in China, highlighting the advantages and disadvantages of various systems in terms of usability and user experience. Combined with the actual needs of hospitals, this paper developed a set of preoperative intelligent measurement system (MIPS) based on pattern recognition for total skeletal joint replacement. It is beneficial for doctors to better observe the lesions of patients before surgery and carry out necessary operations in the PATIENT DR film. In the process, the model is used to identify the patient, and the patient is given a fake score based on the characteristics of the DR film. In nonsymptomatic patients, 13.5% had muscle contraction > 50 %, 2.0% had muscle contraction 70%, and the mean pelvic area was 23.48%. The left ventricular muscle has a 45.0% contraction rate, the left ventricle has a 70% contraction, and the median contraction rate is 47.58%. The right muscle, which is inserted between the right artery and the inner lymphatic artery, is the most common type of compression of the right muscle, accounting for 59.26%. In terms of the mean muscle contraction rate on the right side, patients with DVT with right muscles were higher than patients with DVT with left ventricles (48.54% to 22.29%, P < 0.001 ). The mean incidence of left ventricular DVT patients was higher than that of right ventricular DVT patients (71.88% versus 45.83% P < 0.0011 ).